Efektivitas Pemberian Ekstrak Daun Jati Belanda (Guazuma Ulmifolia Lam) terhadap Kadar CRP pada Tikus Wistar Model Kontusio Pulmonum - Nadhif, Aufa Muhammad; Kamaluddin, M. T.; Theodorus, Theodorus (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Guazuma ulmifolia Lam is a plant with high flavonoid and phenol content. Both of these substances can provide antioxidant effects that are good for the treatment of pulmonary contusions. The aim of the study was to determine the efficacy of Guazuma ulmifolia Lam leaves extract on CRP levels in wistar rats in pulmonary contusion models. In vivo study, pre-post test only has been done in Animal House Faculty of Medicine Sriwijaya University in the period from November to December 2019. There were 25 male Wistar strain rats and divided into five groups, each group consisting of five mice. Mice are induced pulmonary contusions by dropping a load from a certain height. after that, rat blood was taken to be examined for pre-treatment CRP levels. Rats were treated according to the group for 48 hours, then their blood was taken to be examined for post-treatment CRP levels with ELISA. Data was analyzed using SPSS version 25. The rats weight and CRP levels are homogen. Guazuma ulmifolia Lam leaves extract showed significant results in reducing CRP levels in all groups compared with the control group.. The administration of the Guazuma ulmifolia Lam leaves extract (Guazuma ulmifolia Lamk) in rats with pulmonary contusions can reduce serum CRP levels.